Experimental study on the bearing property of the composite foundation with stiffened deep cement mixing pile based on the PHC pile - Feng, Tao; Huiqiang, Zhu; Fengbo, Dong; Shaoqiang, Chai; Feng, Liu; Ming, Zhang (Frontiers in Materials, 2023)
Inserting a prestressed high-intensity concrete pipe pile into a cement–soil mixing pile can form a new composite pile named the composite foundation with stiffened deep cement mixing (SDCM) pile. The Huanghuai alluvial stratum in China is selected to carry out the in situ test for the SDCM pile, and the bearing capacity of the SDCM pile is tested by the slow-speed maintenance load method. The results show that for an SDCM pile with dense silt and fine sand as the bearing layer, the characteristic value of bearing capacity can reach 2,300 kN, which means an SDCM pile with a length of 8.0 m meets the load requirement of a general high-rise building. Further analysis shows that the SDCM pile saves more than 40% of the cost compared with the traditional CFG pile and has better quality control advantages at the same time. This research can provide basic data and design references for similar site foundation projects.